The boundary conditions of the hypersensitive agency detection device: an empirical investigation of agency detection in threatening situations - Maij, David L. R. (Religion, brain & behavior, 2019)
It has been hypothesized that humans have evolved a hypersensitivity to detect intentional agents at a perceptual level, as failing to detect these agents may potentially be more harmful than incorrectly assuming that agents are absent. Following this logic, ambiguous threatening situations should lead people to falsely detect the presence of agents. In six threat-inducing experiments (N = 233) we have investigated whether threat induction increases agent detection. We operationalized human agent detection by means of a Biological Motion Detection Task (Experiments 1 and 2) and an Auditory Agent Detection Task (Experiment 4). Intentionality detection was operationalized by means of a Geometrical Figures Task (Experiment 3). Threat manipulations that were either weak (threatening pictures, classical horror music) or moderate (virtual reality) did not increase false human agent or intentionality detection. Moreover, participants generally had a response bias towards assuming that agents were absent (Experiments 1a, 1b, 2a, 2b, and 4). Further, agent and intentionality detection measures were unrelated to individual differences in supernatural beliefs, although they were related to the negativity bias. This study reveals the boundary conditions under which the agent and intentionality detection is not intensified and provides recommendations for future research.